Utopian Rhythms: Ralph Ellison and the Jazz Aesthetic - Megan Rust Mustain (Revista Espaço Acadêmico, 2018)
This essay explores the utopian notion of freedom at work in Ralph Ellison’s major writings and, following the cues laid out in his essays on literature and music, traces the process of the realization of freedom to a recognition of the rhythmic nature of history. Ellison finds the key to this recognition in aesthetic creation, exemplified in the performative aspects of writing fiction and making music. These creative acts, which take the past as both irrevocable and mutable, strive to recapitulate the rhythms of experience in such a way as to make them rise to the level of consciousness. To explore the extent to which such acts are liberating, I focus on Ellison’s notion of history as it ties in with other aspects of African-American culture. In particular, the notions of repetition and rhythm come to the fore. I examine the extent to which the rhythmic resonance of historically created ideals or principles constitutes the primary significance of the past – in short, its life in the present. Using Ellison’s fiction and elements of the jazz tradition, I seek to use this understanding of rhythm to find a sense of utopia, or perhaps in a more tempered sense of possibility within the irrevocability of the past. I begin by discussing various ways of coming to terms with repetition and, homing in on the notion of repetition as rhythm, examine the interrelations of rhythm and improvisation, actuality and possibility, history and freedom.